The relationship between net farm income, cash rents, and land values in Kansas - Gibson, Heather N. (Kansas State University, 2015)
Land value research has been conducted over many decades with efforts being focused on a broad spectrum of topics encompassing many different issues. The research in this thesis will focus on understanding the relationship between net farm income, cash rent, and land value. This research could provide insight and direction in determining future land value behavior. Understanding land prices is important to many different segments of the agricultural industry. Those involved in the industry want to know where land values are going and what the future looks like. Although certain segments may not be directly affected by land value movements, if value decreases the environment of the agriculture industry is changed. Farmers and ranchers are interested in future land values as they make purchase and sale decisions or as they consider future growth of their operation. Agribusinesses understand the affect a decrease in land value would do to farmer’s decisions regarding capital purchases. Additionally, agriculture finance institutions are interested in the future movement of land value as they are concerned about the affects adverse movements in land value would have on their customer’s balance sheet and ultimately their collateral position. In this paper the relationship between land value and cash rent; where land value is a function of historical cash rent and cash rent is a function of net returns to the land will be tested for its’ existence in Kansas. Data were collected for the nine crop reporting districts in Kansas from 1973 through 2012.
Keywords: Land value; Cash rent; Net farm income; Kansas land valuation model; Economics, Agricultural (0503)